2022
DOI: 10.1002/adma.202200272
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Energy Absorption Mechanisms of Architected Liquid Crystal Elastomers

Abstract: A unique rate‐dependent energy absorption behavior of liquid crystal elastomer (LCE)‐based architected materials is reported. The architected materials consist of repeating unit cells of bistable tilted LCE beams sandwiched between stiff supports. The viscoelastic behavior of the LCE causes the energy absorption to increase with strain rate according to a power‐law relationship, which can be modulated by changing the degree of mesogen alignment and the loading direction relative to the director. For a strain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 26 publications
1
39
0
1
Order By: Relevance
“…Jeon et al recently reported that the energy absorption density of architected LCE materials increases with strain rate according to power-law relationship. 211 With this newly obtained knowledge, they achieved a 5 MJ m À3 energy absorption density at a strain rate of 600 s À1 , which is two orders of magnitude higher than previously reported results.…”
Section: Biomedical Applicationsmentioning
confidence: 57%
“…Jeon et al recently reported that the energy absorption density of architected LCE materials increases with strain rate according to power-law relationship. 211 With this newly obtained knowledge, they achieved a 5 MJ m À3 energy absorption density at a strain rate of 600 s À1 , which is two orders of magnitude higher than previously reported results.…”
Section: Biomedical Applicationsmentioning
confidence: 57%
“…Impressio’s helmet prototype contains liquid crystal elastomers housed within 3D printed columns [ 71 , 74 ]. Liquid crystal elastomers combine the self-organization of the liquid crystalline phase with the elasticity of an elastomer, offering an innovative and potentially superior approach to absorbing impact energy [ 75 77 ]. All three companies incorporated 3D printing into their design with an increased focus on the customization of helmet fit for each individual.…”
Section: Innovations In Helmet Designmentioning
confidence: 99%
“…77,80 Liquid crystal elastomers combine the self-organization of the liquid crystalline phase with the elasticity of an elastomer, offering an innovative and potentially superior approach to absorbing impact energy. [81][82][83] All three companies incorporated 3D printing into their design with an increased focus on the customization of helmet fit for each individual. Experimental evaluation is ongoing.…”
Section: Innovations In Helmet Designmentioning
confidence: 99%